World affairs. - American Peace Society. (American Peace Society., 1837)
Includes the Annual report of the American Peace Society.
Issues for 1837-May 1911 were published in Boston [etc.]
Irregularities in volume numbering.
Includes the Annual report of the American Peace Society.
Later issues also available on the World Wide Web.
Keywords: Peace / fast / (OCoLC)fst01055758; International relations / fast / (OCoLC)fst00977053; Arbitration (International law) / fast / (OCoLC)fst01761738; Arbitration (International law) / Periodicals.; Peace / Periodicals.; International relations / Periodicals.; Periodicals / fast / (OCoLC)fst01411641